Chapter 7 Underlying beliefs about writing and teaching writing in Germany An analysis of policy documents for German in Year 9 at secondary school - Müller, Nora (Taylor & Francis, 2021)
Assumptions about good writing and teaching writing have undergone various changes during the last century. This chapter summarises relevant changes in Germany's approaches to teaching writing and then uncovers underlying values and beliefs about writing in current German policy documents by focusing on Hauptschule Year 9, where students can achieve the first general education qualification that entitles apprenticeship admission. In particular, we analyse national Educational Standards and a sample of federal Curricula by drawing on discourses of writing (DoW) and learning to write outlined by Ivanič (2004). Although there are clear variations among federal states, a common denominator is the dominance of the genre and skills discourses. At the same time, there is a lack of consistent references to discourses relating to process-oriented writing and creativity. The sociopolitical and social practices DoW are completely absent. We show that the focus on genre and skills can partly be explained by Germany's educational legacy but also by the growing emphasis on output orientation in educational policy documents, which is accompanied by writing assessments focused on aspects of literacy that are easier to evaluate (e.g., reading and orthography). We argue that policy documents need to be more closely connected to values and beliefs of what constitutes good writing by current writing scholars.